Pharmacokinetics and anticoagulant properties of the factor VIIa-tissue factor inhibitor recombinant Nematode Anticoagulant Protein c2 following subcutaneous administration in man - Vlasuk, George P.; Bradbury, Annette; Lopez-Kinninger, Lily; Colón, Sonia; Bergum, Peter W.; Maki, Steven; Rote, William E. (Thrombosis and Haemostasis, 2003)
Recombinant Nematode Anticoagulant Protein c2 (rNAPc2) is a potent (Ki=10 pM), inhibitor of the factor VIIa/tissue factor (fVIIa/TF) complex that requires the prerequisite binding to zymogen or activated factor X (fX). In two double blind, placebo-controlled, sequential dose-escalation phase I studies, rNAPc2 was found to be safe and well tolerated following single and repeat subcutaneous administrations in healthy human male volunteers at doses ranging from 0.3 to 5 µg/kg. There was a dose-dependent elevation of the prothrombin time reaching almost 4-fold above the baseline value in the highest dose group that directly correlated with rNAPc2 plasma concentration. In contrast, there was little or no effect on the activated partial thromboplastin time, thrombin time or template bleeding time. The pharmacokinetic behavior of rNAPc2 revealed a dose-independent and prolonged elimination half-life (t1/2β) with a mean of >50 hours. A high affinity interaction between rNAPc2 and plasma fX was shown to be essential for the prolonged t1/2β in man using crossed immunoelectrophoresis and was confirmed by exploiting the considerably weaker interaction between rNAPc2 and bovine fX which resulted in an attenuated t1/2β of ~1.5 hours in calves. The accumulated data suggests that rNAPc2 is safe and well tolerated following repeat subcutaneous administrations at doses up to 5 µg/kg in healthy volunteers. In addition, the in vivofate of rNAPc2 in man appears to be governed by its high affinity interaction with circulating fX. This data supports the continued development of this novel anticoagulant for the prevention and treatment of acute thrombotic disorders.
Keywords: rNAPc2; Factor VIIa; tissue factor; pharmacokinetics; anticoagulant